Historical Discussion and Reflection on the Latinization of Chinese Characters - Wanruo, Luo (Sinología hispánica. China Studies Review, 2024)
In the history of Chinese character reform, there was a movement to abolish Chinese characters that lasted for more than half a century, involving almost all the elites and intellectuals of the whole society. The trend of Latinization of Chinese characters still leaves many traces in people’s daily life today. By sorting out the development process of the Latinization of Chinese characters in history, this paper discusses the profound political, economic and cultural reasons behind it, to explain the irreplaceability of ancient Chinese characters, and its adaptability to China’s national conditions in the long history.